Caracterização físico-química e culinária na predição da qualidade de grãos de arroz de terras altas - Moreira, Adriane Maranho (2012)
The evaluation of cooking and sensory characteristics of a particular cultivar is an important attribute for rice grain quality, in order to direct the decisions by the breeding programs and to allow the prediction of its market acceptance. The target population of this study was originated from a cross between two upland rice cultivars, BRS Primavera and Douradão, chosen in order to add to descendent genotypes the desirable grain quality of the first with the favorable agronomic profile of the second. The objective of this research was to propose a methodology for evaluating the quality of grain from that upland rice segregating population under different storage conditions, to optimize line selection in rice breeding programs focused on rice table. The grains were harvested in 2010 in Santo Antonio de Goiás, milled and analyzed for apparent amylose content, gelatinization temperature, rice flour paste viscosity and cooking test. The results were used to calculate the Pearson correlation coefficient (r). The ANOVA was performed by applying the "F" distribution of Fischer- Snedecor, adopting a significance level of 5%. The physicochemical characterization performed showed the existence of heterogeneous families. The observed changes in the physicochemical and cooking characteristics prove that time and temperature of storage promote modifications on chemical and physical properties of the grain, being the grain cohesiveness reduction the most pronounced change. From the use of the proposed methodology, it was possible to perform the pre-selection of accesses in the target population, by reducing at least 76% the number of resulting samples for final selection. Only 5% of the progeny were pre-selected for the five treatments simultaneously. Indirect analysis recommended for the characterization of rice cooking quality for direct consumption did not provide the desired setting with the cooking test, showing the need for greater integration of generated results and the application of more refined sensory test; on the other hand, they present themselves as appropriate to allow the pre-selection of accesses by this methodology. The methodology proposed in this study showed to be a useful tool in the pre-selection of individuals, and may also be adapted in the pre-selection of lines for other purposes in breeding programs of rice culture and even for other cultures.